The Feasibility of the Southeast Asian Bloc as a Common Currency Area - Satkunaseelan, Shaheelan (2008)
This paper aims to test the feasibility of Malaysia, Singapore and Brunei in forming a common currency area, dubbed the Southeast Asian Bloc. This paper draws inspiration from the works of Ngiam and Yuen in defining the Southeast Asian bloc. The paper starts with an overview of the current literature on optimal currency areas, and other feasibility studies done on the area of forming a common currency area. Using three different tests, the three countries are tested to check for convergence in its exchange rate, which gives an indication of the suitability of forming a common currency area. Another country, Thailand, is also tested to determine its suitability for inclusion in this Bloc. An analysis of key macroeconomic variable is also conducted to complement the conducted tests. Evidence from the tests indicates that there is convergence in the exchange rates of Malaysia, Singapore and Brunei. However the tests do indicate that Thailand is not suitable for the inclusion into the Southeast Asian Bloc. This is followed by an analysis of the historical relationship between Malaysia, Singapore and Thailand, with the intention on shedding some light on the reason for the convergence of the exchange rates of these countries. Arguments to and for the formation of the common currency area is presented, with mention on the political will needed to form the common currency area.